2016
DOI: 10.1103/physrevlett.116.235301
|View full text |Cite
|
Sign up to set email alerts
|

Observation of 2D Fermionic Mott Insulators ofK40with Single-Site Resolution

Abstract: We report on the site-resolved observation of characteristic states of the two-dimensional repulsive Fermi-Hubbard model, using ultracold 40 K atoms in an optical lattice. By varying the tunneling, interaction strength, and external confinement, we realize metallic, Mott-insulating, and bandinsulating states. We directly measure the local moment, which quantifies the degree of on-site magnetization, as a function of temperature and chemical potential. Entropies per particle as low as 0.99( 6) kB indicate that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
103
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 37 publications
(58 reference statements)
0
103
0
Order By: Relevance
“…Already, Mott-insulating phases and short-range antiferromagnetic correlations have been observed, but temperatures were too high to create an antiferromagnet [12][13][14][15]. A new perspective is afforded by quantum gas microscopy [16][17][18][19][20][21][22][23][24][25][26][27][28], which allows readout of magnetic correlations at the site-resolved level [25][26][27][28]. Here we report the realization of an antiferromagnet in a repulsively interacting Fermi gas on a 2D square lattice of approximately 80 sites.…”
mentioning
confidence: 99%
“…Already, Mott-insulating phases and short-range antiferromagnetic correlations have been observed, but temperatures were too high to create an antiferromagnet [12][13][14][15]. A new perspective is afforded by quantum gas microscopy [16][17][18][19][20][21][22][23][24][25][26][27][28], which allows readout of magnetic correlations at the site-resolved level [25][26][27][28]. Here we report the realization of an antiferromagnet in a repulsively interacting Fermi gas on a 2D square lattice of approximately 80 sites.…”
mentioning
confidence: 99%
“…A study comparing these four methods consistently found striped states at 1 8 doping [43]. The DMET has also been used to map the density-interaction phase diagram of the Hubbard 2469-9950/2018/97(7)/075112 (10) 075112-1 ©2018 American Physical Society model showing (co)existence of stripe states and d-wave superconductivity [44], and AFQMC has been used to study long wavelength stripes at low doping [45]. The existence of the stripe state is also being debated for the closely related t-J -model, where stripes have been studied using iPEPS [46], variational monte carlo [47], and fixed-node Monte Carlo (FN) methods [48].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental methods for realizing the Hubbard Hamiltonian have also been developed in the ultracold gas community [3][4][5]. Especially, the recent development of the fermionic quantum gas microscopes provides an interesting platform for observing magnetic order [6][7][8][9][10][11][12][13][14][15], although further advances are needed to reach the possible superconducting phases.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to traditional solid state systems, quantum gases feature tunable spin polarization, dimensionality, and interaction strength. This enables the separation of quantum statistical effects from interaction-driven effects, and invites the exploration of rich phase diagrams, for example bulk Fermi gases in the BEC-BCS crossover [3][4][5][6][7][8][9][10] and Fermi-Hubbard models in optical lattices [11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%